EARLY INCISIONAL HERNIA AFTER LIVER TRANSPLANTATION: RISK FACTORS AND HERNIA REPAIR RESULTS - João Victor Vecchi Ferri; Sofia Michele Dick; Tomaz de Jesus Maria Grezzana-Filho; Flávia Heinz Feier; Lucas Prediger; Glória Sulczinski Lazzaretti; Cleber Rosito Pinto Kruel; Carlos Otavio Corso; Leandro Totti Cavazzola; Marcio Fernandes Chedid (ABCD: Arquivos Brasileiros de Cirurgia Digestiva, 2022)
ABSTRACT BACKGROUND: Liver transplantation is a complex and valuable therapy. However, complications that burden postoperative quality of life, such as incisional hernia, are to be better elucidated, such as risk factors and prophylactic measures. AIM: This study aimed to define the rate of incisional hernia in patients who underwent liver transplantation in a population in southern Brazil and to assess the related risk factors in order to establish measures for prior optimization and specific prophylactic care in the future. METHODS: Patients undergoing adult Liver transplantation from January 2004 to November 2020 were retrospectively analyzed, assessing demographic features, surgical outcomes, and predisposing factors. RESULTS: Among 261 liver transplantation patients included, incisional hernia was diagnosed in 71 (27.2%). Of the 71 incisional hernia patients, 28 (39.4%) developed IH during the first post-transplant. Majority of the patients were male (52/71, 73.2%); of the 71 patients, 52 had hepatitis C virus (HCV) and 33 (46.5%) had hepatocellular carcinoma (HCC). Male gender (p=0.044), diabetes mellitus (p=0.008), and acute cellular rejection (p<0.001) were risk factors for IH. In all, 28 (39.4%) patients were submitted for hernia repair with mesh, with a recurrence rate of 17.8%. CONCLUSION: Incisional hernia after liver transplantation is a relatively common problem associated with male gender, diabetes, and acute cellular rejection. This is a problem that should not be trivialized in view of the complexity of liver transplantation, as it can lead to a reduction in quality of life as well as jeopardize late liver transplantation results and lead to incarceration and strangulation.